Antigen characterization of vector-borne and cultured metacyclic trypomastigotes of Trypanosoma cruzi - N. Yoshida; M. M. G. Teixeira; C. A. Sbravate (Revista do Instituto de Medicina Tropical de São Paulo, 1986)
Metacyclic trypomastigotes ol the CL strain of Trypanosoma cruzi obtained from triatomid vectors and from axenic cultures were comparatively analysed as to their antigen make-up and immunogenic characteristics. They were found to be similar by the various parameters examined. Thus, sera of mice immunized with either one of the two metacyclic types precipitated a 82Kd surface protein from 131I-labeled culture metacyclics. Sera of mice protected against acute T. cruzi infection by immunization with killed culture metacyclics of a different strain (G) recognized, by immunoblotting, a 77Kd protein in both types of CL strain metacyclics. A monoclonal antibody raised against G strain metacyclics, and specific for metacyclic stages of this strain, reacted with both CL strain metacyclic types. Both metacyclic forms were similarly Iysed by various anti-T. cruzi sera, in a complement-mediated reaction.